AN INTEGRATIVE MODEL OF FINANCIAL DECISION MAKING: THE MEDIATING ROLE OF FINANCIAL MANAGEMENT BEHAVIOR BETWEEN RISK PERCEPTION AND FINANCIAL ATTITUDE - Nilawati; Felisitas Defung; Wirasmi Wardhani (CV. Radja Publika, 2026)
Financial decision-making in public organizations is complex because of accountability pressures and environmental uncertainty. This study aimed to examine the influence of risk perception and financial attitude on financial decisions, with financial management behavior as a mediator. A quantitative approach was used with an explanatory design and structural equation modeling–partial least squares analysis on data from regional government organization employees. The results indicate that risk perception and financial attitude have significant positive effects on financial management behavior and financial decisions. Financial management behavior is proven to be the strongest determinant and partial mediator, linking psychological factors to financial decisions. These findings confirm that financial decisions are influenced not only by cognitive evaluations but also by concrete management behavior. The research contribution lies in the integration of the behavioral finance approach and the theory of planned behavior in the public sector context. Practical implications emphasize the importance of strengthening financial management behavior to improve the quality of rational and accountable decisions.